Mothers' Experiences with Child Protection Services: Using Qualitative Feminist Poststructuralism - Megan Aston; Sheri Price; Martha Paynter; Meaghan Sim; Joelle Monaghan; Keisha Jefferies; Rachel Ollivier (MDPI AG, 2021)
Background: The postpartum period is often portrayed as a blissful, calm and loving time when mothers, partners and family members bond with their newborn babies. However, this time may be experienced quite differently when mothers are monitored by Child Protection Services. Having a baby under these circumstances can be very difficult and traumatizing. While all new parents require support and information to help them through the transition to parenthood and address physical and psycho-social changes, mothers who are involved with Child Protection Services require more specialized support as they encounter higher incidences of postpartum stressors and higher rates of poverty, mental illness and substance abuse. The impact of support for mothers involved with Child Protection Services is not well-understood from the perspective of mothers. Aim: The aim of the study was to understand how new mothers in Nova Scotia prioritized their postpartum needs and where they went to obtain information and support. Methods: Feminist poststructuralism was the methodology used to understand how the experiences of five mothers who accessed a family resource center and had been involved with Child Protection Services in Nova Scotia Canada had been personally, socially and institutionally constructed. Results: Themes include: (1) We are Mothers, (2) Being Red Flagged, (3) Lack of Trust, (4) Us Against Them and (5) Searching for Supportive Relationships. Conclusion: Personal stories from all participants demonstrated how they experienced stigma and stereotypes from healthcare workers and were often not recognized as mothers. They also struggled to find information, supports and services to help them keep or regain their babies.